WATER CONSERVATION: RAIN WATER HARVESTING PROJECT FOR DHARUR VILLAGE - Miss Namrata Anna Garad; Prof. Hangargekar; Prof. D. C. Poul; Prof. S. C. Wadne (International Journal of Innovations in Engineering Research and Technology, 2023)
The Paper deals with the study of water requirement, water availability and collection of rainwater for the selected colony. The method adopted was rain water harvesting and groundwater recharge. The research work started with collection of the data of rainfall and calculations of roof area for the analysis, followed by analyzing quantity of water collected from the roof top. Considering this quantity storage capacity of underground water tank is substituted and size for the same is calculated. Simultaneously design of collection system, distribution system is calculated. The study was conducted in “Dharur” village is situated in this drought prone area of Maharashtra. This is at high altitude and having average annual rainfall of 761 mm. For the water supply of water for “Dharur Village Lake” is main sources used. Data collection also includes collection of basic data of the village such as population of the village, no of bore well, roof area, average rainfall and coefficient of runoff. The main objective was to minimize the duplication of ground water table as extraction from those will reduces and to reduce load on water treatment plant as demand decreases.